PERSPECTIVES OF THE DEVELOPMENT OF DARK TOURISM AT THE SITES OF GENOCIDE IN BELGRADE - Todorov, Predrag; Mijuk, Nenad (The Business of Tourism, 2023)
Abstract: Dark tourism, or visits to places marked by death, violence and suffering, is an increasingly important component of the modern tourist experience. Genocide sites, which are witnesses of historical atrocities and tragedies, offer great tourist potential in Belgrade. This paper analyzes the perspectives of the development of dark tourism in such places in Belgrade. Through the analysis of cultural, sociological and economic aspects, the work examines the possibilities of integrating dark tourism into the existing tourist offer, with a special focus on preserving the authenticity of these locations and educating visitors and local residents about historical events and the moral implications of the visit. The paper also discusses the challenges and opportunities for raising awareness about the importance of remembering the victims and promoting sustainable tourism at the genocide sites in Belgrade. Through this analysis, the paper identifies the significant tourism potential of dark tourism in Belgrade and calls for the planned development and preservation of these locations in order to enable visits, education and honoring of the victims, which would contribute to the local and global understanding of historical events.